Age and Experience as Determinants of Managerial Information Processing and Decision Making Performance - Taylor, Ronald N. (Academy of Management Journal, 1975)
Differences in managerial decision making performance due to age and decision making experience were investigated. Age was found to influence performance more than did prior decision making experience. Little evidence was found to support the notion that older managers are less facile information processors and decision makers.